An Analysis of the Advantage Effect of Sports Health Industry Clusters and Research on the Optimisation of Public Service Systems Based on Complex Network Theory - Zhuo Yao,; Mingyuan Cao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The collaboration between economic units in the sports health industry leads to increased efficiency compared to individual businesses. Additionally, the concentration of these units in a specific region promotes division of labor and cooperation within the industry. The current body of research on the sports health industry, which encompasses both public welfare and commercial aspects, remains inadequate. Specifically, there is a lack of information on how to establish a robust and efficient public service system that can contribute positively to the growth of sports health industry clusters. For this reason, this article examines the positive impact of the sports health industry cluster and investigates the improvement of the public service system using complex network theory. It also establishes a network for expanding the sports health industry cluster, providing a basis for further analysis and research. An extensive public service system was established for the sports health industry cluster, allowing for a thorough quantitative analysis of its impact. A new three-stage mathematical envelope analysis model was developed to assess the overall efficiency of the newly established basic industrial capacity of the sports health industry cluster. In this report, we present the analysis results of various sports health industry clusters and public service systems. We examine the growth and impact of sports health industry clusters under different circumstances and put forth several recommendations to enhance the spillover effect of innovative technology and improve the quality of scientific and technological services. To optimise the industrial chain at the base, it is crucial to strengthen cooperation between enterprises at the core network level. This will contribute to the advantage effect analysis of the sports health industry cluster and the optimisation of the publishing service system.